Comparative morphology of Bornean species of ansonia (amphibia : anura : bufonidae) - Esther Sheren, Anak Joseph (unimas, 2012)
This project focused on the species of the genus Ansonia (family Bufonidae), which are also known as „slender toads‟. The genus distributed over Southeast Asia, and Borneo houses 12 species. These are A. albomaculata, A. hanitschii, A. leptopus, A. longidigita, A. minuta, A. spinulifer, A. fuliginea, A. guibei, A. platysoma, A. torrentis, A. echinata and including the recently rediscoverd (2011) A. latidisca. The objectives of this study are to discriminate between species by using morphology and morphometric parameters, and enhance identification keys for the genus. The results of Discriminate Function Analysis (DFA) showed that the strongest characters to discriminate the species are the ratio length of the head and warts type. By using only numerical data, A. guibei and A. minuta can be distinguished. By using binary data, A. spinulifer showed distinct group. For both analyses of Cluster analysis using ratios and raw data, failed to completely separate all the species into groups except for A. spinulifer. This may due to small sample size of some species and overlapping characteristics between species. Taxonomic keys are enhanced to identify all the species in the genus.